Allometric multilevel modelling of agility and dribbling speed by skeletal age and playing position in youth soccer players - Valente-dos-Santos, J.; Coelho e Silva, M. J.; Duarte, J.; Pereira, J.; Rebelo-Gonçalves, R.; Figueiredo, A.; Mazzuco, M. A.; Sherar, L. B.; Elferink-Gemser, M. T.; Malina, R. M. (International Journal of Sports Medicine, 2014)
This study evaluates the contributions of age, skeletal maturation, body size and composition, training and playing position to the development of agility and dribbling speed in young male soccer players (10-18 years) followed longitudinally. 83 players [defenders (n=35), midfielders (n=27), forwards (n=21)] were followed annually over 5 years (average: 4.4 observations per player). Skeletal age (SA), stature, body mass, triceps and subscapular skinfolds, agility and dribbling speed were measured annually. Body composition was estimated from the 2 skinfolds. Annual training volume was estimated from weekly participation forms completed by coaches. The multiplicative allometric models with the best statistical fit showed that statural growth of 1 cm predicts 1.334 s and 1.927 s of improvement in agility and dribbling speed, respectively. Significant independent effects of fat-free mass and annual volume training were found for agility and dribbling speed, respectively (P<0.05). Predicted agility (from 12 to 18 years of SA) and dribbling speed (from 13 to 18 years of SA) differed significantly among players by playing positions (midfielders>forwards>defenders). The present results provide developmental models for the interpretation of intra- and inter-individual variability in agility and dribbling speed among youth soccer players across adolescence, and may provide a framework for trainers and coaches to develop and evaluate individualized training protocols.